The systemic toxicity of heavy metal mixtures in rats. Issue 3 (29th January 2018) - Fiati Kenston, Samuel Selorm; Su, Hong; Li, Zhou; Kong, Lu; Wang, Yafei; Song, Xin; Gu, Yuanliang; Barber, Tabatha; Aldinger, Joni; Hua, Qihang; Li, Zhen; Ding, Min; et al.
Abstract : To explore the health effects of multi-heavy metal exposure, Sprague Dawley (SD) rats were orally given one dose of heavy metal mixtures (HMMs). Abstract : To explore the health effects of multi-heavy metal exposure, Sprague Dawley (SD) rats were orally given one dose of heavy metal mixtures (HMMs). The eight most common detectable heavy metals in Ningbo area are zinc (Zn), copper (Cu), manganese (Mn), chromium (Cr), nickel (Ni), cadmium (Cd), lead (Pb) and mercury (Hg). In this study, mixtures of these eight heavy metals were prepared using the compounds zinc sulfate heptahydrate, cupric sulfate, manganese dichloride, potassium dichromate, nickel dichloride, cadmium dichloride, lead acetate, and methyl mercury chloride with ion mass proportions of 1070.0, 312.6, 173.1, 82.6, 30.0, 13.3, 6.6, and 1.0, respectively. The rats were randomly divided into four groups. Beside the control group, each rat received a corresponding dose of HMMs 215, 464 or 1000 mg per kg body weight (bwt), respectively. The rats were observed for 4 weeks. During the last week of observation, the Morris water maze test was used to investigate spatial learning and memory in the treated rats. The rats were exsanguinated under complete chloral hydrate anesthesia and organ coefficients were measured. Biochemical tests of blood and serum samples were carried out. The results showed abnormalities in the hematological system, decreased renal function, hepatic injury and disturbances in the electrolyte balance of the rats treated with a high dose of HMMs. Death of some rats was also observed. This paper analyzed how a one-time high dose oral administration of HMMs induced systemic toxicity.